Trichogoniinae, a new subtribe of Eupatorieae (Asteraceae) - Lopes Rivera, Vanessa; Da Costa Ferreira, Silvana; Panero, Jose L. (Phytotaxa, 2016)
We describe subtribe Trichogoniinae in tribe Eupatorieae to include three genera, Platypodanthera, Trichogonia, and Trichogoniopsis. Molecular phylogenetic results provide support for the taxonomic limits of the new subtribe. Morphological synapomorphies for the three genera include a pappus of plumose to subplumose bristles and cypselae with narrow stipitate bases. Subtribe Trichogoniinae is part of a clade whose generic and species diversity is mostly found in the Cerrado and Atlantic Forest of South America. A key to the genera of the subtribe is provided.